Search for Selection Signatures Related to Trypanosomosis Tolerance in African Goats - Serranito, Bruno; Taurisson-Mouret, Dominique; Harkat, Sahraoui; Laoun, Abbas; Ouchene-Khelifi, Nadjet-Amina; Pompanon, François; Benjelloun, Badr; Cecchi, Giuliano; Thevenon, Sophie; Lenstra, Johannes A.; Da Silva, Anne (Frontiers in Genetics, 2021)
Livestock is heavily affected by trypanosomosis in Africa. Through strong selective pressure, several African indigenous breeds of cattle and small ruminants have acquired varying degrees of tolerance against this disease. In this study, we combined LFMM and PCAdapt for analyzing two datasets of goats from West-Central Africa and East Africa, respectively, both comprising breeds with different assumed levels of trypanotolerance. The objectives were (i) to identify molecular signatures of selection related to trypanotolerance; and (ii) to guide an optimal sampling for subsequent studies. From 33 identified signatures, 18 had been detected previously in the literature as being mainly associated with climatic adaptations. The most plausible signatures of trypanotolerance indicate the genes DIS3L2, COPS7B, PD5A, UBE2K, and UBR1. The last gene is of particular interest since previous literature has already identified E3-ubiquitin ligases as playing a decisive role in the immune response. For following-up on these findings, the West-Central African area appears particularly relevant because of (i) a clear parasitic load gradient related to a humidity gradient, and (ii) still restricted admixture levels between goat breeds. This study illustrates the importance of protecting local breeds, which have retained unique allelic combinations conferring their remarkable adaptations.